The figure of the Witness in present-day Phaenomenology - Mena Malet, Patricio Andrés (Estudios de Filosofía, 2009)
The following essay searches for a definition of the scopes and possibilities of a Hermeneutical Phenomenology of the Witness in the work of Paul Ricoeur. Two objectives give shape to this first approach. 1) To establish the place of the Witness in the frame of Contemporary Phenomenology, particularly Husserl`s, Sartre`s and Lévinas; 2) To question the Passive Condition of the Witness, condition which, to our judgment makes of him a respondent, inscribing ricoeurian work, with all due cautions, which shall be many, in the beginning of what we could call the advance of many attempts to conduct a Phenomenology of Responsiveness (Jean-Louis Chrétien, Emmanuel Housset, Claude Romano). Each particular attempt case, nonetheless, is so singular and original that a proof would be needed of their coincidences or lack of them. In this sense, this essay is a prolegomenon to a future one which would have as its task seriously considering each of these French Phenomenologists.